Enhanced closed-loop systematic kinematics analysis of wheeled mobile robots. (16th July 2019) - Han, Ziyong; Yuan, Shihua; Li, Xueyuan; Zhou, Junjie
The traditional homogeneous transform maintains central position in the kinematic modelling of robotics. However, for these kinematic modelling of wheeled mobile robots over uneven terrain, the homogeneous transform that represents angular velocity implicitly in the time derivative of the rotation matrix has a drawback in orientation representation. In this article, to improve the angular representation, a new general systematic method for kinematics modelling and analysis of wheeled mobile robot is proposed. The approach uses the Sheth–Uicker convention and loop-closure kinematic chains to derive the position, velocity and acceleration kinematics. The screw coordinates are used to reform the velocity kinematics to centroidal kinematics; then, the Jacobian calculation is simplified to solve the screw vector algebra equations instead of the matrix equations. Meanwhile, the linear and angular components of the centroidal kinematics are endowed with physical meanings and are easy to be selected as control variables. The approach is applied to a wheeled mobile robot, and its effectiveness is verified by the simulation results with various terrain.